Broadening the avenues of complementary medicine and way forward to integrate it with evidence-based modern medicine research – A need of the hour - Pal, Anjali; Panigrahi, Sunil K; Santra, Archismita (Indian Journal of Community Health, 2025)
This scoping review explores the evolving role of complementary and traditional medicine (TC&M) in modern healthcare systems, emphasizing the need for evidence-based practices to facilitate their integration into conventional medical research and practice. Complementary medicine refers to health practices which are not main-stream like modern medicine used along with conventional medicine, contributing to holistic health by addressing physical, mental, and social well-being. Despite their widespread use, particularly in underserved and resource-constrained settings, TC&M lacks rigorous scientific validation, hindering its acceptance and integration into mainstream healthcare. The review outlines the historical evolution of TC&M, citing key milestones such as the establishment of dedicated research institutions like the National Center for Complementary and Alternative Medicine (NCCAM) and WHO recommended strategies on Traditional Medicine. It also highlights the challenges of integrating TC&M due to the lack of research data, financial support, and standardized practices. Furthermore, the review identifies the growing need for evidence-based approaches, particularly in countries like India, where traditional systems such as AYUSH (Ayurveda, Yoga, Unani, Siddha, and Homeopathy) are widely practiced. To achieve Universal Health Coverage (UHC) and address the growing burden of non-communicable diseases, the review advocates for a shift toward integrative medicine, combining modern and complementary approaches. It stresses the importance of collaborative research, standardized training for healthcare professionals, and the development of global frameworks to evaluate TC&M practices. Ultimately, this integration could improve healthcare accessibility, reduce costs, and enhance overall health outcomes.